Influence of electrodes substrate material for diamondlike films deposition on the quality of bioanalysis - Семеній, Олександр Михайлович; Рожицкий, Микола Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
The main objective of the research is determining the influence of substrate material for deposition of diamond-like films on the coating quality, as well as its further behavior as an electrode in electrochemical sensor for bioliquids analysis. Electrochemistry of aqueous-solutions and atomic force microscopy were used as the methods for the research. The obtained results led to the following conclusions. Molybdenum can be applied only when using it at the cathode. Platinum substrate caused the sample cracking, but since the gaps are sufficiently large, they can be used as microelectrode. Glassy carbon sample showed the best properties. The coating was uniform, without breaks and punctures. During the electrochemical studies, the sample showed the widest range of working potentials. These properties are the most applicable for various biosensors where a wide area of ideal polarizability in aqueous solutions is required.